24a+-22=-4(1+6a)

Simple and best practice solution for 24a+-22=-4(1+6a) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 24a+-22=-4(1+6a) equation:


Simplifying
24a + -22 = -4(1 + 6a)

Reorder the terms:
-22 + 24a = -4(1 + 6a)
-22 + 24a = (1 * -4 + 6a * -4)
-22 + 24a = (-4 + -24a)

Solving
-22 + 24a = -4 + -24a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '24a' to each side of the equation.
-22 + 24a + 24a = -4 + -24a + 24a

Combine like terms: 24a + 24a = 48a
-22 + 48a = -4 + -24a + 24a

Combine like terms: -24a + 24a = 0
-22 + 48a = -4 + 0
-22 + 48a = -4

Add '22' to each side of the equation.
-22 + 22 + 48a = -4 + 22

Combine like terms: -22 + 22 = 0
0 + 48a = -4 + 22
48a = -4 + 22

Combine like terms: -4 + 22 = 18
48a = 18

Divide each side by '48'.
a = 0.375

Simplifying
a = 0.375

See similar equations:

| p=2(89)+2(117) | | -2x-3=x+3+3x | | (x+3)+2(x-7)=3x-11 | | a(10)-8=-24 | | 2y^2+4y-198=0 | | 18-43=4(x-2)-5 | | 9x-(4x-15)=50 | | 2(4r+6)=12r+18 | | 8-9=-12 | | 3z+1=4z-8+28 | | 12(x-9)=-5-7 | | 8=(x+0.5)(x+1) | | x*x+10x=1575 | | 3x-64-32x=6 | | x+50+2x+20=90 | | -6k+7k-9k+8k= | | x+50+2x+20=180 | | 2370=320*144*15*x/35000 | | 49a^4b-14a^3b+21ab=0 | | -2(-3x+8)+5=-21 | | 4x-70=12x+2 | | 6(3a+1)-30=3(20a-4) | | 16=(x+0.5)(x+0.5) | | 2h-35=12h-10h+15 | | 2x+7x+10=11x | | x+2+x+4+x^2-3x+3x-2=39 | | 12c^2-13c-35= | | 10x=9x-25 | | -9-6k+9-(2k)= | | .2m=22 | | -8h+3(1-5)=3b+37 | | 6(7y-5)=12y |

Equations solver categories